Step-Down of FSH- Dosage During Ovarian Stimulation – Basic Lessons to Be Learnt From a Randomized Controlled Trial - Lawrenz, Barbara; Coughlan, Carol; Melado, Laura; Digma, Shieryl; Sibal, Junard; Jean, Alliza; Fatemi, Human M. (Frontiers in Endocrinology, 2021)
A rise in serum progesterone in the late follicular phase is a well described adverse effect of ovarian stimulation for IVF/ICSI. Previous data suggest, that enhanced gonadotropin stimulation causes progesterone elevation and the incidence of premature progesterone elevation can be reduced by declining gonadotropin dosages. This randomized controlled trial (RCT) aimed to achieve a significant reduction of the progesterone level on the day of final oocyte maturation by a daily reduction of 12.5 IU rec-FSH from a follicle size of 14 mm in a GnRH-antagonist protocol. A total of 127 patients had been recruited (Control group (CG): 62 patients; Study group (SG): 65 patients). Due to drop out, data from 108 patients (CG: 55 patients; SG: 53 patients) were included into the analysis. Patients’ basic parameters, gonadotropin (Gn)-starting dose, total Gn-stimulation dosage, the number of retrieved and mature oocytes as well as in the hormonal parameters on the day of trigger (DoT) were not statistically significantly different. However, through stepwise Gn-reduction of 12.5 IU/day in the SG, there was a statistically highly significant difference in the Gn-stimulation dosage on the day of trigger (p < 0.0001) and statistically significant associations for the DoT-P4-levels with the DoT-FSH-levels for both groups (CG: p = 0.001; SG: p = 0.0045). The herein described significant associations between DoT-P4-levels and DoT-FSH-levels confirm the theory that enhanced FSH stimulation is the primary source of progesterone elevation on the day of final oocyte maturation in stimulated IVF/ICSI cycles. Given the pathophysiologic mechanism of progesterone elevation during ovarian stimulation, the use of an increased FSH step-down dosage should be studied in future RCTs, despite the fact that a step-down approach of daily 12.5 IU rec-FSH did not achieve a significantly reduced progesterone level on the DoT.